Crystallographic analysis of the Staphylococcus epidermidis lipase involved in esterification in aqueous solution. Issue 6 (5th June 2018) - Liu, Cheng-Huan; Chen, Yu-Ting; Hou, Ming-Hon; Hu, Nien-Jen; Chen, Chin-Shuh; Shaw, Jei-Fu
Abstract : Crystals of the GehC protein from Staphylococcus epidermidis that diffracted X‐rays to a resolution of at least 1.9 Å are described. Abstract : The Staphylococcus epidermidis lipase (SeLip, GehC) can be used in flavour‐compound production via esterification in aqueous solution. This study reports the crystallization and crystallographic analysis of recombinant GehC (rGehC; Lys303–Lys688) with a molecular weight of 43 kDa. rGehC was crystallized at 293 K using PEG 10 000 as a precipitant, and a 99.9% complete native data set was collected from a cooled crystal at 77 K to a resolution of 1.9 Å with an overall R merge value of 7.3%. The crystals were orthorhombic and belonged to space group P 21 21 21, with unit‐cell parameters a = 42.07, b = 59.31, c  = 171.30 Å, α = β = γ = 90°. Solvent‐content calculations suggest that there is likely to be one lipase subunit in the asymmetric unit.